O voto como instrumento da ressocialização no cumprimento de medida socioeducativa de internação - Guazzelli, Murilo Carvalho Pereira (2011)
Without distancing itself from a restriction of freedom, this work aims to present an instrument able to, on a concrete way, attend the constitutional principle of the system of integral protection by the moment of the social educative measurement of internment. Therefore, through the notion of citizen determined by the Social Democratic Law State, there is an attempt to settle the vote as such mechanism, making possible, as a result, the preservation of a fundamental right, as it is the right to vote, in addition to the dignity of the human being. It will be demonstrated by the end that the awaited resocialization of the teenagers doing time related to the social educative measurement of internment will only be possible by the time such teenagers are seen as people subject to rights. And also seen as citizens able to influence the result of the voting, which will certainly call the attention of the public authorities. Otherwise, the internment will be no more than a mere criminal sanction that will result in the social isolation and in the maintenance of non-citizens; but never on a sanction able to generate public politics which will concretely promote the resocialization of the teenager confronting the law